Inside the world of diplomacy : the U.S. Foreign Service in a changing world - Finger, Seymour Maxwell, 1915-2005 (Praeger, 2002)
Ambassador Seymour Finger provides an insider's view of American diplomacy since World War II, including many of its leaders, and of the changing American Foreign Service. He also offers proposals to equip the Foreign Service for the challenges of the 21st century.